Literature Review: Pengaruh Kemoterapi Terhadap Nilai Leukosit dan Trombosit Pada Penderita Kanker Payudara - Andi Fitra Pramesti Regina Cahyani; Aji Bagus Widyantara; Yuyun Nailufar (JURNAL RISET RUMPUN ILMU KEDOKTERAN, 2025)
Cancer is a disease caused by the abnormal growth of body tissue cells. Breast cancer is one of the leading causes of death for women worldwide. The 5-year survival rate approaches 97% when tumor cells are confined to breast tissue and drops dramatically to 23% when tumor cells have metastasized to other organs at the time of diagnosis. Myelosuppression is a side effect of chemotherapy in cancer patients. Myelosuppression is a decrease in the number of hemoglobin, platelets, neutrophils, and leukocytes below normal, leading to anemia, thrombocytopenia, neutropenia, and leukocytopenia. This study aims to determine the effect of chemotherapy on leukocyte and platelet counts in breast cancer patients. This study is a qualitative descriptive study that describes the research topic data using a similar approach to the topic of the literature review. The results of this study indicate that most breast cancer patients undergoing chemotherapy experience a decrease in platelet and leukocyte counts